Earmuffs for everyone! : how Chester Greenwood became known as the inventor of earmuffs - McCarthy, Meghan (Simon & Schuster Books for Young Readers, 2014)
"This picture-book biography of Chester Greenwood explores the invention of the earmuffs and the patenting process"--